MSLI-Net: retinal disease detection network based on multi-segment localization and multi-scale interaction - Qi, Zhenjia; Hong, Jin; Cheng, Jilan; Long, Guoli; Wang, Hanyu; Li, Siyue; Cao, Shuangliang (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe retina plays a critical role in visual perception, yet lesions affecting it can lead to severe and irreversible visual impairment. Consequently, early diagnosis and precise identification of these retinal lesions are essential for slowing disease progression. Optical coherence tomography (OCT) stands out as a pivotal imaging modality in ophthalmology due to its exceptional performance, while the inherent complexity of retinal structures and significant noise interference present substantial challenges for both manual interpretation and AI-assisted diagnosis.MethodsWe propose MSLI-Net, a novel framework built upon the ResNet50 backbone, which enhances the global receptive field via a multi-scale dilation fusion module (MDF) to better capture long-range dependencies. Additionally, a multi-segmented lesion localization module (LLM) is integrated within each branch of a modified feature pyramid network (FPN) to effectively extract critical features while suppressing background noise through parallel branch refinement, and a wavelet subband spatial attention module (WSSA) is designed to significantly improve the model’s overall performance in noise suppression by collaboratively processing and exchanging information between the low- and high-frequency subbands extracted through wavelet decomposition.ResultsExperimental evaluation on the OCT-C8 dataset demonstrates that MSLI-Net achieves 96.72% accuracy in retinopathy classification, underscoring its strong discriminative performance and promising potential for clinical application.ConclusionThis model provides new research ideas for the early diagnosis of retinal diseases and helps drive the development of future high-precision medical imaging-assisted diagnostic systems.